Investigations of Corrosion Effects at High Temperatures and High Pressure Conditions - Abdulwahhab, Yousuf (Curtin University, 2020)
Corrosion in the oil and gas industry is one of the outstanding challenging problems due to material degradation. This thesis deals with the nature of the passive film formed on 316LSS and its protective mechanism in oil and gas production where anaerobic CO2 environments exist as well as high temperature and pressure. In addition to the effect of different CO2 partial pressure. This thesis are also study the effects of nitrite ions on the corrosion inhibition of carbon steel in the absence and presence of chloride solution at high temperature.